SLANG TERMS USED IN THE EXPENDABLES 3 MOVIE DIRECTED BY PATRICK HUGES - Nuraeni, Cicih; Restianafari, Yulia Karine; Umam, Akhmad Hairul (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2021)
Slang can not only be found in daily conversation but it also can be found in literary work such as movies, for example in The Expendables 3 Movie which the characters’ use slang quite often in dialogues. The purpose of this paper is to study the function, type, and meaning of the slang terms used by the characters of The Expendables 3 movie. The researchers used descriptive qualitative method to analyze. After doing the analysis, the researchers found fifty-five slang terms and the details are as follows: (1) There are two types of slang, namely primary and secondary slang. The type which more often used is primary slang. (2) There are three types of functions: social, psychological and rhetorical functions (3) There are seven types of meaning of slang namely connotative, social, affective, collocative, conceptual, thematic and reflection meanings. Connotative meaning is the most common